2003
DOI: 10.1017/s0025315403007707h
|View full text |Cite
|
Sign up to set email alerts
|

Changes in benthic community structure due to clam dredging on the Algarve coast and the importance of seasonal analysis

Abstract: Patterns in community structure of meiofauna and macrofauna in relation to Portuguese clam dredging were compared during a 2-y-period o¡ Lagos and Vilamoura, south Portugal. SCUBA divers randomly sampled corer and quadrat samples before and immediately after simulating commercial dredge ¢shery. Univariate measures (abundance, number of taxa, evenness, diversity and biomass) and multivariate analyses (Cluster, MDS and SIMPER) revealed changes in the meio-and macro-benthic community structure caused by dredge di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Moreover, during a previous study on polychaete assemblages in the Bering Sea, Yeung et al (2010) attributed high abundances of Aphroditidae to an environment that was frequently disturbed by trawling and fish discards. Likewise, increased Aphroditidae abundance was observed off Portugal after 2 years of experimental dredging (Alves et al 2003). Bed KSH 1 has consistently been the most heavily dredged scallop bed in the North Pacific and exhibited the starkest spatial differences in community composition within our study region, with lower CPUEs for all taxa except Paguridae and Aphroditidae.…”
Section: Anthropogenic Correlatessupporting
confidence: 53%
See 1 more Smart Citation
“…Moreover, during a previous study on polychaete assemblages in the Bering Sea, Yeung et al (2010) attributed high abundances of Aphroditidae to an environment that was frequently disturbed by trawling and fish discards. Likewise, increased Aphroditidae abundance was observed off Portugal after 2 years of experimental dredging (Alves et al 2003). Bed KSH 1 has consistently been the most heavily dredged scallop bed in the North Pacific and exhibited the starkest spatial differences in community composition within our study region, with lower CPUEs for all taxa except Paguridae and Aphroditidae.…”
Section: Anthropogenic Correlatessupporting
confidence: 53%
“…Weak correlations with dredging across a wide range of substrate types may be explained by a combination of factors, namely (1) high interannual variability in dredging effort, (2) our inclusion of both motile and sessile fauna that may respond to disturbance differently, and (3) the fact that most beds are represented by a mix of soft substrates. Although there is strong evidence that scallop dredging reduces diversity (Collie et al 1997;NRC 2002;Alves et al 2003), habitat type affects the level of impact and recovery rate from dredging (Collie et al 2000;Kaiser et al 2006). In previous work examining the effects of scallop dredging on soft-bottom habitat in the Gulf of Alaska, significant but minimal differences in epifaunal benthic community abundance and species diversity existed between areas that were open and closed to trawling and dredging (Stone et al 2005).…”
Section: Anthropogenic Correlatesmentioning
confidence: 99%
“…The fact that previous studies recorded considerable amounts of bycatch in the bivalve dredge fisheries along the Algarve coast, even exceeding the catch of the target species in late spring and early summer (Gaspar and Chícharo 2007), reinforces the importance of the present study and the need for further investigation on this important subject. Other studies have reported seasonal trends in the bycatch collected by mechanical bivalve dredges: namely an increase in flatfish discards in autumn on the Algarve coast (Palma et al 2003), possibly associated with greater abundances in benthic communities in this area during this season (Alves et al 2003), and also higher discards of D. trunculus in spring and summer in the northern Alboran Sea (Urra et al 2017).…”
Section: Discussionmentioning
confidence: 88%
“…According to the cluster analysis, calculated values showed that species diversity (H') in Şile region was higher in autumn (AS) when compared to the other seasons and other region, and this may be as a result from the fishing season (Autumn is the beginning of fishing season in Turkey after four months of fishing closure). Alves et al (2003) highlighted that after dredging activity abundance, number of taxa, evenness, diversity and biomass showed a decrease in Portugal clam dredging trials. Gaspar et al (2003) announced that the abundance of hermit crabs may not be regarded as a universal monitoring tool in identifying fishing areas because of the aggregation of scavengers, such as hermit crabs, in fished areas can last from a few minutes (Gaspar et al, 2003) to a few days (Jenkins et al, 2004); in this study D. pugilator, a scavenger, was a good discriminator for G1 (in SIMPER).…”
Section: Discussionmentioning
confidence: 95%